Apple: creative destruction and the Icarus dilemma - Pennings, Johannes (Henry Stewart Talks, 2017)
The case study describes how Apple developed the Mac computer in a separate business unit from the rest of Apple’s operations. This enabled Apple to develop a completely new and successful product, while also saving itself from the Icarus dilemma.